Aloe vera Oil-Added Agar Gelatin Edible Films for Kashar Cheese Packaging - Isık, Isılay; Yenipazar, Hande; Saygun, Ayse; Sahin Yesilcubuk, Nese; Ozkan Zayim, Esra; Catalgil Giz, Huceste (American Chemical Society (ACS), 2023)
In recent years, there has been a growing interest in edible and biodegradable films due to their sustainability, environmental friendliness, and their functionality. In this work, Aloe vera oil-added agar-gelatin films were prepared and characterized in terms of water content, degree of swelling, water solubility, antioxidant activity, and antimicrobial activity. The possibility of using these edible films for Kashar cheese packaging during cold storage was investigated. Physical, chemical, and microbiological properties of the packaged cheese samples were examined for 20 days of cold storage at 4 °C. A. vera oil-added films were found to have antibacterial activity against Escherichia coli and Staphylococcus aureus and antifungal activities against Aspergillus niger and Candida albicans. A. vera oil-added films showed high antioxidant activities, increasing with the increasing A. vera oil percentage in the formulation. The current study showed that at the end of 20 days of storage period, bacterial growth in A. vera oil-incorporated film-covered samples was 2.30 log CFU/g lower than the control samples, and the amount of yeast and mold in A. vera oil-added film-covered samples was 3.37 log CFU/g lower than control samples. This shows the efficiency of A. vera oil-incorporated agar-gelatin films during the refrigerated storage period. Our data evidenced the positive effect of A. vera oil-added agar-gelatin films on Kashar cheese packaging as an innovative and sustainable technique to maintain cheese quality and prevent food loss during storage.